Protein profiles of parental varieties and hybrids of rice and their correlation with heterosis - de Oliveira, Antonio Costa; Derbyshire, Eric; Carvalho, Maria Teresa V.; Ando, Akihiko (Pesquisa Agropecuaria Brasileira, 1993)
Two Japanese and five Brazilian cultivars of rice (Oryza sativa L.), were analyzed for morphological and protein traits and the hybrids from their crosses were also evaluated for heterosis and heterobeltiosis. The protein traits in combinations, as well as the morphological traits permitted to discriminate at the individual level. The protein profiles determined under dissociating conditions and the acid phosphatase profiles (FAC), and the morphological characters number of productive tillers, number of grains per plant, grain production and days to flowering (DPF), differed between the Japanese and Brazilian groups. The number of productive tillers, number of grains per plant and DPF showed significant correlations with production both for cultivars and for hybrids. Quantitative differences in the relative intensity of esterase activity among the parental cultivars and hybrids and, as a smaller factor, qualitative differences in the acid phosphatase profiles were related to heterobeltiosis for grain weight. All the hybrids with positive heterobeltiosis for grain weight were derived from crosses between the Japanese cultivar Senshou and Brazilian cultivars. The total undissociated protein permitted to differentiate each of the fourteen samples analyzed, however the combination of protein characters gives a more secure basis for discrimination.